Motyw szaleństwa w opowiadaniach Brunona Schulza. Studium psychologiczno-literackie - Sienkiewicz, Barbara; Sienkiewicz-Wilowska, Julia Anastazja (My University, 2013)
Representation of various modes, forms, symptoms and degrees of mental illnesses, frequent in "The Street of Crocodiles", are analysed in two perspectives: psychological and literary-cultural. Using the tools of modern psychology, the article interprets the pathological symptoms of Touya, Maria, aunt Agatha, and various other characters, most importantly the advancing illness of father Joseph, who displays symptoms of schizophrenia. Schulz uses a language filled with metaphors, blurring the border between symptoms of illness and metaphors, between the imaginary and the real, and between health and illness, norm and pathology, between the human and the animal. Schulz’s representation of madness opposes the modern understanding, which is dominated by analytical, rationalist identification of an illness, related to a socially determined norm of mental health. It brings back the premodern quality to madness, which becomes a divine phenomenon, related to the pagan rite of fertility, to the “orgy of life” and Dionysian element, and to Freudian life drive. Dionysius and Freud meet in an area independent from the rules of culture and reason: the return to nature, including the nature in a human being. Here, madness becomes a “basic figure” and “the ultimate ur-schema”, as they belong to the unintellectual, basic, ecstatic sphere. This is related to the imperative of penetration of areas that threaten the “balance of the soul”, to address the topic that shows “the scar of removal”, and forces us to ask the question of limits of humanity.
Motive of Madenss in Schulz’s Short Stories. A Psychological-Literary Study
Keywords: Dionysus; modernity; life drive; premodernity; organic society; madness